Fabrication of dense Ce0.9Mg0.1P2O7-PmOn composites by microwave heating for application as electrolyte in intermediate-temperature fuel cells - Singh, Bhupendra; Devi, Nitika; Mathur, Lakshya; Singh, Rajesh K.; Bhardwaj, Aman; Song, Sun-Ju; Henkensmeier, Dirk (ELSEVIER SCI LTD, 2018)
In the present work, we report a method of fabrication of dense 10 mol% Mg2+-doped cerium pyrophosphate phosphate (Ce0.9Mg0.5P2O7-PmOn; CMP-P) composites by microwave heat-treatment of the preformed Ce0.9Mg0.1P2O7 substrates in the presence of phosphoric acid. The composite was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). The microwave heating at 375 degrees C for 5 min resulted in the formation of dense CMP-P composites which retained most of the pyrophosphate phase. The electrical conductivity was extracted from the EIS data and for the CMP-P composite prepared by H3PO4 loading for 10 h and microwave heat-treatment for 5 min it was found to be > 10(-2) S m(-1) in 100-250 degrees C range with a maximum of 0.062 S cm(-1) at 190 degrees C, which was significant for its application as electrolyte in intermediate temperature fuel cells.